Системні чинники грошово-кредитної політики та їх вплив на мікро- та макроекономічні процеси в Україні - Волоснікова, Наталія Миколаївна (НТУ "ХПІ", 2018)
У статті розглянуто закономірності впливу грошово-кредитної політики на мікро- та макроекономічні процеси економіки України. Проведено дослідження теорії і практики категорії "грошово-кредитний ринок". Узагальнено теоретичні підходи до визначення сутності грошово-кредитного ринку. Проведено оцінювання та аналіз динаміки основних макроекономічних показників та складових грошово-кредитного ринку. Проаналізовано основні проблеми розвитку грошово-кредитного ринку та представлено способи вирішення.

In the article regularities of influence of monetary and credit policy on micro- and macroeconomic processes in the economy of Ukraine are considered. A study of theory and practice of the category "Monetary market" was conducted. Generalized theoretical approaches to determining the essence of the monetary market. The estimation and the analysis of dynamics of the basic macroeconomic indicators and components of the monetary market is carried out. The main problems of the development of the monetary market are analyzed and solutions are presented. The main instruments used by the National Bank of Ukraine for conducting monetary policy are considered. The ways of improving the regulation of monetary policy are suggested. The process of developing and adopting the basic principles of monetary policy has been explored. The problematic aspects of ensuring the stabilization of the monetary and credit market in conditions of instability are outlined.
System factors of money-credit policy and their influence on micro- and macroeconomic processes in Ukraine
Keywords: грошово-кредитна політика; грошово-кредитний ринок; макроекономічні процеси; мікроекономічні процеси; monetary policy; micro and macroeconomic processes; monetary market